Asupan Karbohidrat Harian terhadap Risiko Kejadian Diabetes Melitus Gestasi (GDM) melalui Glyco-Hemoglobin Ibu Hamil - Def Primal; Tetra Anestasia Putri; Wira Meiriza (Jurnal Keperawatan Silampari, 2021)
This study aims to identify the relationship between the amount of carbohydrate intake in pregnant women in the third trimester with the incidence of gestational diabetes mellitus (GDM) in the health office area of the City of Bukittinggi. This research method is a cross-sectional study using an experimental approach. The results showed that the daily intake of carbohydrates (grams) of pregnant women in the third trimester had a significant relationship with the incidence of GDM in the working area of the Bukittinggi City Health Office based on 34 pregnant women who had been examined. This can be seen from the higher the daily intake of carbohydrates for pregnant women, the increase in the percentage value of HbA1c. In conclusion, there is a correlation between the consistent daily intake of carbohydrates and the HbA1c weight, which refers to pre-diabetes status and gestational diabetes in the third trimester of pregnant women. Keywords: Carbohydrate Intake; Gestational Diabetes Mellitus; HbA1c